DEVELOPMENT OF ADMINISTRATIVE PROCEEDINGS IN THE CONTEXT OF ECONOMIC GLOBALISATION - Maksym Korniienko; Marat Koval; Yurii Pavliutin (Baltic Journal of Economic Studies, 2024)
The subject of the study is the conceptual, theoretical, empirical and methodological foundations of the socio-economic and legal nature of the development of administrative justice in the context of economic globalisation. Methodology. The study uses general and special methods of cognition. Using the dialectical method, the authors differentiates the essence of the development of administrative justice in the context of economic globalisation on the legal and economic levels according to the relevant criteria. The analysis created the conditions for a multifaceted study of the complex of problems and prospects for the development of Ukrainian administrative justice in the context of economic globalisation from the perspective of economic and legal etymology. The synthesis created the conditions for generalising the characteristic features of administrative justice, taking into account the current trends and international legal and regulatory developments in this area. The formal legal method allowed to correctly interpret the content of international and national legal acts that define the directions for improving administrative justice in the context of economic globalisation. The purpose of the article is to identify the problems and directions of development of administrative justice in the context of economic globalization. The results of the study show that the problems of the current state of administrative justice in Ukraine are complex, and the ways to overcome them take into account various parameters that are directly or indirectly based on the principles of economic globalisation, which are primarily based on economic and legal principles. Among the areas for improvement of administrative procedures, those that primarily ensure effective protection of human rights and freedoms, in particular through the implementation of relevant international standards, occupy an important place. Conclusion. The study of the economic foundations for optimisation of administrative justice in Ukraine has made it possible to identify certain indicators which serve as socio-economic prerequisites for optimisation of administrative justice. The statistical data show that the areas of manifestation of the subject matter of administrative court proceedings are differentiated depending on the impact of economic globalisation on certain public law relations which give rise to the relevant public law disputes. The authors distinguishes between a group of public law disputes which are directly related to the phenomenon of economic globalisation, and public law disputes in which public interests of economic content are manifested. This contributes to the creation of certain, primarily legal, structures which would facilitate the optimisation of administrative proceedings in the context of economic globalisation, which has both an external, international and internal, national format. The above considerations of optimising administrative justice in the context of economic globalisation have made it possible to identify specific problems faced by Ukrainian justice, including administrative justice: 1) organisational; 2) legal support; 3) material, financial and social support of courts and judges; 4) functioning of the institution of judicial governance and self-government; 5) staffing; 6) ensuring access to justice. Among the areas of improvement of administrative justice, the following are considered in detail: implementation of the principles of the rule of law and procedural economy, introduction of digital technologies (elements of artificial intelligence), introduction of alternative forms of pre-trial and post-trial dispute resolution, optimisation of the zonal and territorial location of courts, implementation of international standards of administrative justice, and some others.